Morphological, morphometrical and molecular identification of Meloidogyne incognita in fig (Ficus carica L.) in Costa Rica. - Peraza-Padilla, Walter (2013)
The objective of this study wasto identify species of Meloidogyne associated with two figplantations in Costa Rica. On March 2012 in Pacayas, Cartagoprovince, root-galls were found in two fig plantationsof Ficus carica L. Females, egg-masses and juveniles (J2)of Meloidogyne sp. were extracted from the galled roots.Female perineal patterns were examined and second infectivestages were analyzed morphometrically and molecularlyby PCR-RFLP. The mitochondrial intergenic region (IGS)flanked by the cytochrome oxidase subunit II gene (COII)and the 16S ribosomal gene was amplified. The populationwas identified morphologically, morphometrically and molecularlyas M. incognita. The PCR product obtained withprimers C2F3 and 1108 were 1.7 kb in size. When PCR productswere treated with restriction enzymes they generatedfour fragments of 850, 450, 250 and 150 bp with AluI andtwo fragments of 1300 and 400 bp with HinfI.